Recombinant adeno-associated virus serotype 6 efficiently transduces primary human melanocytes. - Hilary M Sheppard (Public Library of Science (PLoS), 2013)
The study of melanocyte biology is important to understand their role in health and disease. However, current methods of gene transfer into melanocytes are limited by safety or efficacy. Recombinant adeno-associated virus (rAAV) has been extensively investigated as a gene therapy vector, is safe and is associated with persistent transgene expression without genome integration. There are twelve serotypes and many capsid variants of rAAV. However, a comparative study to determine which rAAV is most efficient at transducing primary human melanocytes has not been conducted. We therefore sought to determine the optimum rAAV variant for use in the in vitro transduction of primary human melanocytes, which could also be informative to future in vivo studies. We have screened eight variants of rAAV for their ability to transduce primary human melanocytes and identified rAAV6 as the optimal serotype, transducing 7-78% of cells. No increase in transduction was seen with rAAV6 tyrosine capsid mutants. The number of cells expressing the transgene peaked at 6-12 days post-infection, and transduced cells were still detectable at day 28. Therefore rAAV6 should be considered as a non-integrating vector for the transduction of primary human melanocytes.